Triple Drug Therapy with Proton Pump Inhibitor a Better Option for Helicobacter Pylori Eradication - Lamture Y.R.1, Thavendra Jaglal Dihare2, Varsha Gajbhiye3, Gode Dilip4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: H. Pylori is a gram-negative micro organism residing in the stomach of human. It is aimportant cause of acid peptic disorders. Bismuth based triple therapy,triple therapy regimens(Tripple PPI)and Quadruple therapy are the available treatment options to eradicate H. pylori. Controversy still presentsregarding the superiority of treatment modality and results of available studies are variable. Hence thisstudy was undertaken to evaluate and compare the efficacy of triple PPI, Quadruple therapy, and bismuthbasedtriple therapy in treating acid peptic disorders and Helicobacter pylori eradication. Method: This studywas a prospective interventional. After the establishment of a clinical diagnosis of the acid peptic disorder,the patient was posted for endoscopy. H. pylori status was determined by the rapid urease test and cultureexamination. All patients divided into three groups and offered three different medical treatments the firstgroup received bismuth bases triple therapy, the second group got Tripple PPI therapy and the third onereceived quadruple therapy. efficacy and comparison of all these treatment modalities were evaluated andassessed by symptoms, endoscopic findings, and results of the rapid urease test after 6 weeks. Results: In thepresent study, 150 patients with upper gastrointestinal symptoms were studied It was found that the maximumnumber of subjects belonged to the age group 31-40 yrs. Male outnumbers than females. Maximum patientshad pain in epigastric region and were having gastritis as a commonest diagnosis., Symptomatic relief byTriple therapy with PPI was maximum than other therapies. Rapid urease test (RUT) was also suggest thattreatment with it gives superior eradication rates. Discussion: In our study, we have found that the treatmentregime with PPI Triple therapy has given maximum symptomatic relief, there is an association of H. Pyloriinfection in an acid peptic disorder like duodenal ulcer (86.66%), gastric ulcer (75%), and gastritis (82.85%).the efficacy of the Rapid urease test is 66% and that of culture is 38.66% in the diagnosis of H. pyloriinfection in acid peptic disorder. Conclusion: PPI Triple therapy is most effective in symptomatic relief andhealing of the duodenal and peptic ulcer